Transvaginal fistula flip and ligation for mid-and low rectovaginal fistula: an analysis of 62 cases - Zeng Yixian; He Yinghua; Liu Zhenju; Li Guodong; Wang Xiaofeng (结直肠肛门外科)
[Objectives] To investigate the clinical efficacy of transvaginal fistula flip and ligation for mid-and low rectovaginal fistula. [Methods] This was a retrospective analysis of 62 patients with mid-and low rectovaginal fistula treated with transvaginal fistula flip and ligation at our department between January 2010 and June 2020. Surgical details and postoperative follow-up were collected. [Results] Of the 62 patients, the median duration of surgery was 60 (30, 90) minutes; median time to the first postoperative bowel movement was 3 (2, 4) days; median postoperative catheters duration was 5 (3, 6) days; median duration of hospitalization was 16.0 (14.0, 21.3) days. Eight patients with prophylactic stoma did not undergo stoma reversal following rectal cancer surgery, and the stoma is protective. The median duration of postoperative follow-up was 48.0 (12.8, 87.0) months. Fourteen patients were lost to follow-up. Among the 48 patients who completed the follow-up, 31 were considered cured, and 17 were considered not cured, with no severe postoperative complications. Among patients considered not cured, two underwent transvaginal stapler closure of fistula at one year postoperative and experienced no vaginal flatulence and defecation; the remaining 15 patients did not undergo subsequent repairment surgery and experienced mild symptoms of vaginal flatulence. [Conclusion] Transvaginal fistula flip and ligation show satisfactory overall efficacy for mid-and low rectovaginal fistula. It is a relatively simple and safe procedure.